Analyzing and visualizing Thoracic Surgery Data Set - Bashath, Samar; Ismail, Amelia Ritahani (Universiti Malaya, 2018)
Recently, the need for machine learning for prediction process is increasing. Creating model for a high number of variables could produce overfitting which affects the accuracy of prediction. For that, this paper focus on analyzing the data before creating models using various statistical test between variables.